Ovarian Cancer Targeted Theranostics - Nimmagadda, Sridhar; Penet, Marie-France (Frontiers in Oncology, 2020)
Ovarian cancer is a leading cause of death from gynecological malignancies. Although the prognosis is quite favorable if detected at an early stage, the vast majority of cases are diagnosed at an advanced stage, when 5-year survival rates are only 30–40%. Most recurrent ovarian tumors are resistant to traditional therapies underscoring the need for new therapeutic options. Theranostic agents, that combine diagnostic and therapeutic capabilities, are being explored to better detect, diagnose and treat ovarian cancer. To minimize morbidity, improve survival rates, and eventually cure patients, new strategies are needed for early detection and for delivering specifically anticancer therapies to tumor sites. In this review we will discuss various molecular imaging modalities and targets that can be used for imaging, therapeutic and theranostic agent development for improved diagnosis and treatment of ovarian cancer.